2019
DOI: 10.1073/pnas.1815016116
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/regulatory T cell axis triggers the development of a tumor-promoting immune environment in chronic inflammation

Abstract: Chronic inflammation’s tumor-promoting potential is well-recognized; however, the mechanism underlying the development of this immune environment is unknown. Studying the transition from acute, tumor-suppressive to chronic, tumor-promoting allergic contact dermatitis (ACD) revealed how tumor-promoting chronic inflammation develops. Epidermis-derived interleukin (IL)-33 up-regulation and its induction of regulatory T cell (Treg) accumulation in the skin preceded the transition from acute to chronic ACD and trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 23 publications
3
63
1
Order By: Relevance
“…This is consistent with most previous studies showing that ILC2s are increased in tumor sites [15]. Previous studies have shown that there may be a large number of pro-inflammatory cytokines such as IL-33 and IL-25 in the tumor microenvironment [44]. Pro-inflammatory cytokines can lead to activation and proliferation of ILC2s [45,46] [31][32][33].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with most previous studies showing that ILC2s are increased in tumor sites [15]. Previous studies have shown that there may be a large number of pro-inflammatory cytokines such as IL-33 and IL-25 in the tumor microenvironment [44]. Pro-inflammatory cytokines can lead to activation and proliferation of ILC2s [45,46] [31][32][33].…”
Section: Discussionsupporting
confidence: 92%
“…Accumulating studies have demonstrated the importance of IL-33/ST2 pathway in regulating immune cell generation and function 12,15 . IL-33 can significantly enhance the recruitment of immunosuppressive immune cells into the tumor site, where these cells have a strong impact on immune microenvironment remodeling 15,17,29,51 . Exogenously administered recombinant mouse IL-33 significantly induces ST2-positive Tregs accumulated in tumor masses.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, neutralizing IL-33 or ST2 by administration of antibodies remarkably decreases the density of ST2-positive Tregs inside tumor masses in CRC-bearing mice 63 . A more recent investigation has showed that the IL-33/Treg axis significantly contribute to the creating of tumor-promoting immune environment as seen in chronic inflammation condition 29 . Pastille E et al further revealed that Tregs in the CRC microenvironment could preferentially upregulate ST2 expression in mice.…”
Section: Discussionmentioning
confidence: 99%
“…IL-33-Treg axis blockade can regulate chronic inflammation through a tumor-promoting immune environment. 61 Moreover, increased IL-33 could recruit tumor-infiltrating ST2 + Treg cells in mouse colon cancer model, 51,62 and Treg ST2KO (St2 knockout) mice had significantly increased CD8 + T cells. 61 Charlotte et al found an anti-tumorigenic role for IL-33 in colon cancer.…”
Section: Colorectal Cancermentioning
confidence: 98%
“…61 Moreover, increased IL-33 could recruit tumor-infiltrating ST2 + Treg cells in mouse colon cancer model, 51,62 and Treg ST2KO (St2 knockout) mice had significantly increased CD8 + T cells. 61 Charlotte et al found an anti-tumorigenic role for IL-33 in colon cancer. IL-33 stimulation induced the migration of colon cancer cells, which was connected with the decrease in macrophage in vitro.…”
Section: Colorectal Cancermentioning
confidence: 98%